Plasmid establishment in competent Haemophilus influenzae occurs by illegitimate transformation. - Pifer, M L (1986)
Establishment of plasmids in naturally competent Haemophilus influenzae is incompatible with transformation via the normal DNA translocation pathways. Instead, establishing plasmids appear to evade the degradation which ordinarily accompanies translocation, arriving as intact double-stranded molecules in the cytoplasm. Evidence is presented that plasmid establishment is a rare illegitimate transformation event which resembles artificial transformation. This process is compared with plasmid marker rescue transformation, and a method for greatly increasing establishment frequency is described.